Lack of education or abuse? - Altın, Ismaıl; Dündar, Ahmet Sedat; Ayaz, Nusret; Bork, Turgay; Sener, Serpil; Celbiş, Osman (My University, 2019)
Child abuse is a significant public health problem nowadays. The case is here presented of an unemployed stepfather, with significant risk factors for child abuse, who caused physical abuse to a child with hot water as a result of incorrect toilet training. In this case, the mother tried to hide the event and as a result of the history taken from the child and findings of lesions in the physical examination, it was learned that these had been made by the stepfather because of urine incontinence. In similar situations to this case, healthcare personnel establishing close communication with the child must pay attention in respect of child abuse, and must inform the authorities in all suspicious cases.
Keywords: Adli Tıp; Genel ve Dahili Tıp; Pediatri